2019
DOI: 10.1016/j.aim.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The Hanna Neumann conjecture for Demushkin groups

Abstract: We confirm the Hanna Neumann conjecture for topologically finitely generated closed subgroups U and W of a nonsolvable Demushkin group G. Namely, we show thatwhered(K) = max{d(K) − 1, 0} and d(K) is the least cardinality of a topological generating set for the group K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Proof A pro-p version of this result is proved in [16,Proposition 5.1]. The same proof works in our case.…”
Section: Proposition 44supporting
confidence: 57%
“…Proof A pro-p version of this result is proved in [16,Proposition 5.1]. The same proof works in our case.…”
Section: Proposition 44supporting
confidence: 57%
“…In the proof of [JS19, Proposition 7.2], it is shown that is an one-relator -module. Thus, we can produce an exact sequence where is a non-trivial cyclic -module.…”
Section: The -Hall Property For Surface Groupsmentioning
confidence: 99%
“…As is a domain, . By [JS19, Corollary 6.2], . Hence, , where is the Euler characteristic of as a -module.…”
Section: The -Hall Property For Surface Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demushkin pro-p groups are Poincare duality pro-p groups of cohomological dimension 2 and can be seen as pro-p analogues of discrete surface groups. Applying the strategy developed in [55], A. Jaikin-Zapirain and M. Shusterman have proved in [58] the strengthened Hanna Neumann conjecture for non-solvable Demuskin pro-p groups. Recall that by Proposition 5.6, if G is an ICC countable group, then Z(R K [G] ) is a subfield of C. Another consequence of Theorem 10.1 is the following result.…”
Section: The Hanna Neumann Conjecturementioning
confidence: 99%